2000
DOI: 10.1038/sj.gene.6363654
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilia is attenuated in experimental colitis induced in IL-5 deficient mice

Abstract: Tissue eosinophilia is a feature of idiopathic inflammatory bowel disease and other forms of colonic inflammation but it is not clear whether the role of eosinophils in the disease process is to contribute to tissue damage. Interleukin 5 (IL-5) stimulates production and activation of eosinophils in vitro and enhances immunoglobulin A (IgA) production. As very little is known about the function of IL-5 in the colon, the aim of this study was to assess its role in colonic inflammation. IL-5 deficient mice were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 15 publications
(18 reference statements)
2
34
1
Order By: Relevance
“…14,52 Eosinophil accumulation in the mucosa is a common feature observed during DSS-induced colitis in mice. 16,17 We and others have previously shown that TLR2 signaling in response to the commensal microflora is important in limiting mucosal injury during DSS colitis. 25,26 TLR2-deficient animals have been shown to have a more severe disease development, with an extended time course and slower recovery after cessation of DSS treatment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…14,52 Eosinophil accumulation in the mucosa is a common feature observed during DSS-induced colitis in mice. 16,17 We and others have previously shown that TLR2 signaling in response to the commensal microflora is important in limiting mucosal injury during DSS colitis. 25,26 TLR2-deficient animals have been shown to have a more severe disease development, with an extended time course and slower recovery after cessation of DSS treatment.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Mediators such as CCL5, LTB 4 , and LTC 4 have also been implicated in models of local eosinophilic inflammation and may have a role in the eosinophilic response noted in DSS colitis. 7 In other models of pathogen-induced eosinophilia, it has been shown that direct stimulation of TLR2 by M. bovis can induce an eosinophilic infiltration into the pleural cavity that is highly dependent on IL-5, CCL11, and the CCL11 receptor CCR3.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In human UC, although the significance of eosinophil infiltration is unclear, the infiltration is significantly less marked in patients requiring surgery than in those responding to medical treatment [22]. In DSS colitis, the degree of eosinophil infiltration does not reflect the severity of the disease or the extent of tissue damage [23]. Eosinophils may act as homeostastic immune modulators and play an anti-inflammatory role, releasing aryl sulfatase B, phospholipase D, histaminase, and other chemical mediators [24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%